Writing for television, radio, and new media - Hilliard, Robert L. (Stamford, Connecticut Cengage Learning, 2015)
Writing for Television, Radio, and New media has been the leading work in its field for more than fifty years. Its frequently updated revisions, including the eleventh edition, combine the best principles and examples of the past with those of contemporary practice. Its thorough coverage of concepts, approaches, and techniques concentrates on the key media formats of commercials; news and sports; documentaries; reality programs; talk shows; interviews; music programs; corporate, educational, and children's formats; and drama and sitcoms. The text also presents basic information that writers need to know about production techniques, demographics, copyrights, and career opportunities. New material on social media allows today's students to understand the continued importance of clear writing and shows them how their digital skills can transfer to career opportunities.
Includes index.
Keywords: Broadcasting -- Authorship; Mass media -- Authorship